The Hepatitis E Virus ORF3 Protein Regulates the Expression of Liver-Specific Genes by Modulating Localization of Hepatocyte Nuclear Factor 4 - Chandra, Vivek; Holla, Prasida; Ghosh, Dhrubaa; Chakrabarti, Debarshi; Padigaru, Muralidhara; Jameel, Shahid (PLOS ONE, 2011)
The hepatitis E virus (HEV) is a small RNA virus and the cause of acute viral hepatitis E. The open reading frame 3 protein (pORF3) of HEV appears to be a pleiotropic regulatory protein that helps in the establishment, propagation and progression of viral infection. However, the global cellular effects of this protein remain to be explored. In the absence of traditional in vitro viral infection systems or efficient replicon systems, we made an adenovirus based ORF3 protein expression system to study its effects on host cell gene expression. We infected Huh7 hepatoma cells with recombinant adenoviruses expressing pORF3 and performed microarray-based gene expression analyses. Several genes down regulated in pORF3-expressing cells were found to be under regulation of the liver-enriched hepatocyte nuclear factor 4 (HNF4), which regulates hepatocyte-specific gene expression. While HNF4 localizes to the nucleus, its phosphorylation results in impaired nuclear localization of HNF4. Here we report that pORF3 increases HNF4 phosphorylation through the ERK and Akt kinases, which results in impaired nuclear translocation of HNF4 and subsequently the down modulation of HNF4-responsive genes in pORF3-expressing cells. We propose that modulation of several hepatocyte specific genes by pORF3 will create an environment favorable for viral replication and pathogenesis.